Alleviation of sea water stress on tomato plants by foliar application of aspartic acid and glutathione - Akladious, Samia Ageeb; Abbas, Salwa Mohamed (Bangladesh Journal of Botany, 2013)
Tomato plants (Lycopersicon esculentum Mill.) treated with 8 and 16% of sea water reduced growth parameters and chemical constituents. Both aspartic acid and glutathione increased plant growth, anthocyanin, ?-tocopherol, ascorbic acid and enzymatic activities. Increased endogenous amino acids led to positive changes in protein electrophoresis and caused obvious changes in anatomical features of the stems. The effect of aspartic acid was superior to that of glutathione in increasing plant growth. Under low saline conditions, maximum plant growth was obtained from plants treated with aspartic acid and 8% of sea water, followed by 4%. Data revealed that antioxidants could partially alleviate the harmful effects of salinity. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15822 Bangladesh J. Bot. 42(1): 31-43, 2013 (June)